Negocjacje między demonami Laplace'a: czyżby niedoskonałość konkurencji doskonałej? - Jakubowski, Rafał; Kuśmierczyk, Paweł (Bargaining between Laplacian Demons : Possible Failure of the Perfect Competition Model?, 2005)
The article was inspired by the results of the laboratory experiments in which a model of competing producers was analysed. At one point of the experiment gains gathered by the producers were surprisingly close to the ones resulting from cooperation, even though producers did not have an opportunity to set any agreement. Could such an cooperation take place in the markets as a result of the perfect knowledge of all the agents? One of the most important assumptions of the perfect competition model is the one of the perfect rationality and perfect knowledge of the economic agents. If the economic agents, as the model assumes, are Laplacian demons should not each one of them become aware of the gains resulting from the cooperation? And if in this model all agents are perfectly rational and common knowledge exists should not cooperation start spontaneously between Laplacian demons? This analysis leads to the conclusion that assumption of perfect rationality can, in fact, tum the model of perfect competition into bilateral monopoly, with two monopolists as an effect of cooperation on both: the demand and the supply side of the market. If the perfect competition model acts as though it was a bilateral monopoly it turns out that the consequences of the model, especially the ones of the equilibrium price, do not necessarily have to hold, as two monopolists can set the price at the different level, depending on their bargaining power. Further theoretical consequences and possible outcomes are analysed in the paper. The conducted analysis shows that fictitious assumptions of perfect knowledge and rationality can theoretically lead to a situation of no competition and indistinct equilibrium price and hence should not be part of the model which is to depict “the perfect competition”.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 9-22